How reliable are SIDS rates?. Issue 10 (21st September 2005) - Sheehan, K M; McGarvey, C; Devaney, D M; Matthews, T
Abstract : There is increasing concern with using SIDS as a diagnosis, especially where the postmortem examination reveals additional findings that may be contributory to the death exclusion. This report shows how varying the criteria for a diagnosis of SIDS significantly alters the SIDS rate in Ireland.